Carbon Price Efficiency : Lock-in and Path Dependence in Urban Forms and Transport Infrastructure - Avner, Paolo; Rentschler, Jun; Hallegatte, Stéphane (World Bank, Washington, DC, 2014)
This paper investigates the effect of carbon or gasoline taxes on commuting-related CO2 emissions in an urban context. To assess the impact of public transport on the efficiency of the tax, the paper investigates two exogenous scenarios using a dynamic urban model (NEDUM-2D) calibrated for the urban area of Paris: (i) a scenario with the current dense public transport infrastructure, and (ii) a scenario without. It is shown that the price elasticity of CO2 emissions is twice as high in the short run if public transport options exist. Reducing commuting-related emissions thus requires lower (and more acceptable) tax levels in the presence of dense public transportation. If the goal of a carbon or gasoline tax is to change behaviors and reduce energy consumption and CO2 emissions (not to raise revenues), then there is an incentive to increase the price elasticity through complementary policies such as public transport development. The emission elasticity also depends on the baseline scenario and is larger when population growth and income growth are high. In the longer run, elasticities are higher and similar in the scenarios with and without public transport, because of larger urban reconfiguration in the latter scenario. These results are policy relevant, especially for fast-growing cities in developing countries. Even for cities where emission reductions are not a priority today, there is an option value attached to a dense public transport network, since it makes it possible to reduce emissions at a lower cost in the future.